2004
DOI: 10.1073/pnas.0403216101
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid influences anteroposterior positioning of epidermal sensory neurons and their gene expression in a developing chordate (amphioxus)

Abstract: In developing chordates, retinoic acid (RA) signaling patterns the rostrocaudal body axis globally and affects gene expression locally in some differentiating cell populations. Here we focus on development of epidermal sensory neurons in an invertebrate chordate (amphioxus) to determine how RA signaling influences their rostrocaudal distribution and gene expression (for AmphiCoe, a neural precursor gene; for amphioxus islet and AmphiERR, two neural differentiation genes; and for AmphiHox1, -3, -4, and -6). Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 59 publications
3
83
2
1
Order By: Relevance
“…During normal development, these cells are scattered along the entire AP axis of the developing general ectoderm and express a combinatorial code of different proneural genes including coe, islet, and err. Treatments with RA and RA antagonist shift the AP distribution of sensory neurons in the general ectoderm and alter the combinatorial code of proneural genes expressed in these cells (Schubert et al, 2004). The effect of RA on the distribution of sensory neurons in the amphioxus general ectoderm is reminiscent of the posteriorizing action of exogenous RA on the lateral line neurons of axolotls (Gibbs and Northcutt, 2004).…”
Section: Neural Crest Placodes and Their Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…During normal development, these cells are scattered along the entire AP axis of the developing general ectoderm and express a combinatorial code of different proneural genes including coe, islet, and err. Treatments with RA and RA antagonist shift the AP distribution of sensory neurons in the general ectoderm and alter the combinatorial code of proneural genes expressed in these cells (Schubert et al, 2004). The effect of RA on the distribution of sensory neurons in the amphioxus general ectoderm is reminiscent of the posteriorizing action of exogenous RA on the lateral line neurons of axolotls (Gibbs and Northcutt, 2004).…”
Section: Neural Crest Placodes and Their Derivativesmentioning
confidence: 99%
“…Thus, while exogenous RA shifts collinear expression of hox genes anteriorly, RA antagonist treatment downregulates transcription of hox genes in the general ectoderm. Moreover, Schubert et al (2004) demonstrated that in the amphioxus general ectoderm the differentiation of sensory neurons is sensitive to RA signals. During normal development, these cells are scattered along the entire AP axis of the developing general ectoderm and express a combinatorial code of different proneural genes including coe, islet, and err.…”
Section: Neural Crest Placodes and Their Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine the evolution of the neural crest Hox code, we must also find out how DR5 elements are involved in transcriptional regulation of amphioxus Hox. Schubert et al (2004) demonstrated that AmphiHox1, 3, and 4 expression are sensitive to exogenous RA in both the neural tube and epidermis. We are currently investigating how RAREs are involved in expression of the neural tube and epidermis of ascidian and amphioxus embryos.…”
Section: Evolution Of the New Hox Code In Vertebratesmentioning
confidence: 99%
“…In addition, this network functions directly in the ASP/otic placode to pattern it. Similarly, in amphioxus, RA functions in patterning of the epidermal sensory organ (Schubert et al, 2004), from which placodes are thought to originate (Holland and Holland, 2001). In vertebrates, otic placode formation depends on signals from a properly patterned CNS (Hans and Westerfield, 2007), and is therefore indirectly dependent on RA and Hox1.…”
Section: Discussionmentioning
confidence: 99%